2002
DOI: 10.4049/jimmunol.169.5.2594
|View full text |Cite
|
Sign up to set email alerts
|

Complement Activates the c-Jun N-Terminal Kinase/Stress-Activated Protein Kinase in Glomerular Epithelial Cells

Abstract: In the rat passive Heymann nephritis model of membranous nephropathy, complement C5b-9 induces sublethal glomerular epithelial cell (GEC) injury and proteinuria. C5b-9 activates cytosolic phospholipase A2 (cPLA2), and products of cPLA2-mediated phospholipid hydrolysis modulate GEC injury and proteinuria. In the present study, we demonstrate that C5b-9 activates c-Jun N-terminal kinase (JNK) in cultured rat GECs and that JNK activity is increased in glomeruli isolated from proteinuric rats with passive Heymann … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 40 publications
1
43
0
Order By: Relevance
“…In an earlier study, we demonstrated that complementinduced activation of JNK is dependent on arachidonic acid release and production of superoxide (32). In contrast to the activation of ERK, cytochalasin D, latrunculin B, and calyculin A did not inhibit complement-induced JNK activation (Fig.…”
Section: A-cmentioning
confidence: 99%
See 1 more Smart Citation
“…In an earlier study, we demonstrated that complementinduced activation of JNK is dependent on arachidonic acid release and production of superoxide (32). In contrast to the activation of ERK, cytochalasin D, latrunculin B, and calyculin A did not inhibit complement-induced JNK activation (Fig.…”
Section: A-cmentioning
confidence: 99%
“…Complementmediated cytolysis was determined by measuring release of lactate dehydrogenase (LDH), similarly to the method described previously (12,32). Specific release of LDH was calculated as [NS Ϫ HIS]/ [100 Ϫ HIS], where NS represents the percent of total LDH released into cell supernatants in incubations with NS, and HIS is the percent of total LDH released into cell supernatants in incubations with HIS.…”
Section: Methodsmentioning
confidence: 99%
“…Each of the MAPK family of proteins, including ERKs, p38 MAPKs, and JNKs, has a demonstrable importance in the pathogenesis of cancer, and each is significantly activated by the MAC with resulting cellular proliferation (51,54,55,61,62). Other oncogenic targets activated by the MAC include the phosphoinositide 3-kinase pathway (55), Ras (63), p70 S6 kinase (51), and the Janus-activated kinase-signal transducer and activated transcription pathway (56).…”
Section: Complement Promotes Oncogenesismentioning
confidence: 99%
“…Incubation of cultured GEC with complement stimulated superoxide production via the NADPH oxidase. The mechanism involves activation of cPLA 2 and release of AA (100).…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%